Pengaruh Kualitas Pelayanan Angkutan Kota Terhadap Kepuasan Dan Loyalitas Penumpang Di Kota Kupang - Oktovianus Edvict Semiun (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2018)
This study is aimed to evaluate the quality of urban transportation service and its impact on passenger satisfaction and loyalty in Kupang city, NTT. Data collection was done by distributing questionnaires to 130 passengers chosen by applying random sampling technique. The survey results were analyzed by IPA method and CSI. Whereas, the relationship between importance, performance and passenger loyalty were analyzed using PLS. The results showed that the public transportation service has not reached satisfactory category with the value of CSI at 57,21% (very poor). The results of the analysis of PLS model revealed that both importance and performance positively affected on passenger loyalty, whereas importance negatively affected the performance.